Solvent Free Twin Screw Processed Silybin Nanophytophospholipid: In Silico, In Vitro and In Vivo Insights - Gasper Fernandes; Sai Lalitha Alekhya Pusuluri; Ajinkya Nitin Nikam; Sumit Birangal; Gautham G. Shenoy; Srinivas Mutalik (MDPI AG, 2022)
Silybin (SIL) is a polyphenolic phytoconstituent that is commonly used to treat liver disorders. It is difficult to fabricate an orally delivered SIL product due to its low oral bioavailability (0.95%). Therefore, the current research focusses on the development of a novel composition of a phospholipid complex, termed as nanophytophospholipid, of SIL by employing a unique, solvent-free Twin Screw Process (TSP), with the goal of augmenting the solubility and bioavailability of SIL. The optimised SIL-nanophytophospholipid (H6-SNP) was subjected to physicochemical interactions by spectrometry, thermal, X-ray and electron microscopy. The mechanism of drug and phospholipid interaction was confirmed by molecular docking and dynamics studies. Saturation solubility, in vitro dissolution, ex vivo permeation and preclinical pharmacokinetic studies were also conducted. H6-SNP showed good complexation efficiency, with a high practical yield (80%). The low particle size (334.7 ± 3.0 nm) and positively charged zeta potential (30.21 ± 0.3 mV) indicated the immediate dispersive nature of H6-SNP into nanometric dimensions, with good physical stability. Further high solubility and high drug release from the H6-SNP was also observed. The superiority of the H6-SNP was demonstrated in the ex vivo and preclinical pharmacokinetic studies, displaying enhanced apparent permeability (2.45-fold) and enhanced bioavailability (1.28-fold). Overall, these findings indicate that not only can phospholipid complexes be formed using solvent-free TSP, but also that nanophytophospholipids can be formed by using a specific quantity of lipid, drug, surfactant, superdisintegrant and diluent. This amalgamation of technology and unique composition can improve the oral bioavailability of poorly soluble and permeable phytoconstituents or drugs.